An Application in Total Quality for Active Teaching by Using Fuzzy Soft Sets - Sabri Abd Al Razzaq, Audia (International Journal of Psychosocial Rehabilitation, 2020)
One of the many applications of fuzzy soft sets, which were produced by Maji et al. [3] and generalized by Majumder and Samanta to solve the uncertainty problems in real life. In this study the concept of fuzzy soft sets is applied in total quality in the active teaching process as an application.